Usulan Perbaikan Kualitas pada Produksi Flanges Pipe dan Rubber Gasket Guna Mengurangi Produk Cacat (Studi Kasus : CV Anugerah Sukses Sejahtera Surabaya) - Rodjak, Moch Fhahrul; Khoiroh, Siti Muhimatul (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
CV Anugerah Sukses Sejahtera is a company that operates in the field of manufacturing flanges and rubber gaskets. The company's production process sets a defect tolerance at 5%. In the production flow there is a process failure or defect that occurs in the production process and increases the tolerance amount above a predetermined limit. From the data that has been collected, researchers can identify the types of defect characteristics using the SPC (Statistical Process Control) method and analyze them using fishbone diagrams, as well as provide suggestions for improvements to the company. Based on the Pareto diagram, it was concluded that the highest percentage of defects was in burry defects at 43.2%, the highest rubber attribute defects were in wrinkles at 36.7% and variable flanges defects were in flatness defects at 44.1%. Based on the processing of samples 1-8, it was found that sample proportions exceeded the control limits of the P flange control chart, namely UCL at week 5 and LCL at week 6, while the other proportions were still in the control stage. The dominant cause of this problem is employees' lack of control over the job desk and lack of maintenance on machines. Thus, the proposed improvement given to the company is to carry out On Job Training for new employees, check the rubber raw materials and flanges raw materials, add LED lighting to each machine and carry out regular machine maintenance scheduling